Parents’ beliefs about the role of Kindergarten in literacy development - Tsirmpa, Chrysoula; Stellakis, Nektarios (International Journal about Parents in Education, 2023)
This study is part of a wider research conducted in 13 state kindergartens in Pyrgos, in Western Greece, during the school year 2017-2018. The purpose was to investigate parents’ beliefs about the role of kindergarten in literacy development. Data collected through semi-structured interviews with twenty mothers and analysed by the method of content analysis. Data analysis revealed that all mothers recognise the role of kindergarten in the socio-emotional development of children but they do not seem to realise its role in the development of language and literacy. In conclusion, parents need to be informed about the role of kindergarten in literacy development, what is important for children to learn before they enter primary school and how they can enhance literacy in family environment. The findings emphasise the importance of a meaningful cooperation between kindergarten teachers and parents. Implications and limitations are discussed.